The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Global Business Expansion
DOI: 10.4018/978-1-5225-5481-3.ch076
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Star Bioscientists on Obtaining Venture Capital for Canadian Dedicated Biotechnology Firms

Abstract: As organizations based on science, dedicated biotechnology firms (DBFs) establish very narrow links with universities and public research institutions in developing their technologies. This chapter examines the influence of DBF relationships with star bioscientists on their venture-capital funding. It proposes a new definition of bioscientists anchored in today's technological practices. It also classifies Canadian bioscientists into four categories to give a national overview of their involvement with DBFs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…But it generally does not constitute leading‐edge research, capable of establishing new paradigms or research trajectories on the world level: among the 188 research groups analyzed in our study, only two ‘star scientists’ could be identified. However, these could stimulate local spin‐offs as well as attract the interest of those local companies that have to compete on the world market (Queenton and Niosi, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…But it generally does not constitute leading‐edge research, capable of establishing new paradigms or research trajectories on the world level: among the 188 research groups analyzed in our study, only two ‘star scientists’ could be identified. However, these could stimulate local spin‐offs as well as attract the interest of those local companies that have to compete on the world market (Queenton and Niosi, 2005).…”
Section: Discussionmentioning
confidence: 99%